INDIVIDUAL EMPOWERMENT FAMILY BENEFICIARIES OF THE PROGRAM KELUARGA HARAPAN DOING INDEPENDENT GRADUATION IN DEPOK CITY - Ananda Ayu Shafira; Fentiny Nugroho (UNIVERSITAS PAKUAN, 2022)
The Indonesian government runs a poverty-relief program known as the Program Keluarga Harapan (PKH). The Program Keluarga Harapan, the program that carries the concept of conditional cash assistance, requires not only the provision of assistance for 'free,' but also a change in behavior or conditions, which is the long-term goal of the assistance scheme that has been provided. The implementation of the independent graduation reflects the state of the beneficiaries, who consciously believe that they can live their lives more independently. This condition means to be described by a question about the individual empowerment of the beneficiary families of the Program Keluarga Harapan (PKH), which conducts independent graduation in Depok City. This research describes the state of individual empowerment at beneficiaries in Depok City, which has declared independent graduation voluntarily. The method used is descriptive-qualitative, with data collected through in-depth interviews (with beneficiaries who conduct independent graduation, assistants, local village heads,) documentation studies, and observations. The research found three internal and one external characteristic that characterizes the beneficiarys empowerment: knowledge, self-confidence, the ability to make choices (agency), and social support from the beneficiarys immediate environment.